The impact of Covid-19 on international destinations of Peru and public policy options - Ponce Villegas, Albert Moises (2021)
In an unprecedented event of global and intersectoral repercussion, the service sector - due to its inherent implication of direct interaction - has been one of the most affected, with the travel industry standing out. Current projections foresee a gradual recovery fraught with much confusion. A fundamental factor that affects the habit of traveling comes from economic income. This, according to projections for Latin America and the Caribbean, would see a considerable loss in the progress achieved in the last two decades. Thus, the volume of potential domestic and interregional demand would see a substantial reduction. In such a scenario, the destinations where the market share is predominantly international would be the most affected. Hence the need for public policies on such geographic spaces and their economic agents. Thus, this article lists public policy options in the labour, financial, domestic demand, as well as market opportunities in a post-pandemic horizon.